Tools for schools : applications software for the classroom - Landolphi, Don.; Turner, Sandra (Belmont, CA : Wadsworth, 1997)
Word processing and writing. Communicating with graphics. Preparing and using slide shows. Desktop publishing. Developing inquiry skills with databases. Problem solving with spreadsheets...
Keywords: Education; Computers; AppleWorks; Computers -- Study and teaching -- United States; Computer-assisted instruction -- United States